Dinamización del patrimonio literario: usos culturales de la leyenda = Dynamization of the Literary Heritage: Cultural Uses of the Legend - Vega Rodríguez, Pilar (Lectura y signo, 2019)
A partir de la investigación del proyecto DLLHO_19, este trabajo reflexiona sobre el valor patrimonial de la leyenda (oral o literaria) y sobre los usos culturales que pueden colaborar a la conservación y dinamización de este activo, junto con la trascendencia del legendario en las investigaciones sobre geografía literaria. Based on the research project DLLHO_19, in this paper we reflect on the heritage value of the legend (oral or literary) and on the cultural uses that can contribute to the conservation and dynamization of this asset, together with the transcendence of the legendary in the investigations on literary geography.